'[S]he could … spare one ample breast for the profit of her owner': white mothers and enslaved wet nurses' invisible labor in American slave markets. (3rd April 2017) - Jones-Rogers, Stephanie
ABSTRACT: This essay examines the market that white mothers created for enslaved wet nurses, the intimate labor that they performed in southern households, and the ways that this market intersected with slave marketplaces in the antebellum era. It argues that white mothers' desires and demands for enslaved wet nurses transformed bondwomen's ability to suckle into a largely invisible, yet skilled form of labor, and created a niche sector of the slave market. In these ways, white mothers were crucial to the commodification of enslaved women's reproductive bodies, their breast milk, and the nutritive and maternal care they provided to white children.